Development of a fluorescent probe library enabling efficient screening of tumour-imaging probes based on discovery of biomarker enzymatic activities. Issue 16 (21st March 2022) - Kuriki, Yugo; Yoshioka, Takafusa; Kamiya, Mako; Komatsu, Toru; Takamaru, Hiroyuki; Fujita, Kyohhei; Iwaki, Hirohisa; Nanjo, Aika; Akagi, Yuki; Takeshita, Kohei; Hino, Haruaki; Hino, Rumi; et al.
Abstract : Efficient methodology to develop tumor-imaging fluorescent probes based on screening with our newly constructed probe library for aminopeptidase/protease (380 probes) and clinical samples has been established. Abstract : Fluorescent probes that can selectively detect tumour lesions have great potential for fluorescence imaging-guided surgery. Here, we established a library-based approach for efficient screening of probes for tumour-selective imaging based on discovery of biomarker enzymes. We constructed a combinatorial fluorescent probe library for aminopeptidases and proteases, which is composed of 380 probes with various substrate moieties. Using this probe library, we performed lysate-based in vitro screening and/or direct imaging-based ex vivo screening of freshly resected clinical specimens from lung or gastric cancer patients, and found promising probes for tumour-selective visualization. Further, we identified two target enzymes as novel biomarker enzymes for discriminating between tumour and non-tumour tissues. This library-based approach is expected to be an efficient tool to develop tumour-imaging probes and to discover new biomarker enzyme activities for various tumours and other diseases.